2021
DOI: 10.1021/acs.orglett.1c01559
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Construction of Polycyclic Indazole Skeletons Bearing Five Consecutive Chiral Centers through an Asymmetric Triple-Reaction Sequence

Abstract: A novel approach for the asymmetric construction of polycyclic indazole skeletons via enamine−imine activation and PCET activation was developed by merging organocatalysis with photocatalysis through an asymmetric triple-reaction sequence. In this process, five C−X bonds and five consecutive chiral centers were efficiently constructed. Differently substituted polycyclic indazole deriatives were successfully constructed with satisfactory results under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In 2018, the Wu group reported the use of CO 2 and the synergistic combination of photoredox and cobalt catalysis to form carboxylate alkynes (114) to access various molecules, including biologically significant heterocycles (Table 5D). 35 In this study, 114 was changed into derivatives of 2-quinolones (115). In the presence of Ir(III) (PC24) and Co(II) dual catalysts and blue LED light irradiation, 58-70% yield of product was obtained.…”
Section: Synthetic Techniques For Quinolinonesmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2018, the Wu group reported the use of CO 2 and the synergistic combination of photoredox and cobalt catalysis to form carboxylate alkynes (114) to access various molecules, including biologically significant heterocycles (Table 5D). 35 In this study, 114 was changed into derivatives of 2-quinolones (115). In the presence of Ir(III) (PC24) and Co(II) dual catalysts and blue LED light irradiation, 58-70% yield of product was obtained.…”
Section: Synthetic Techniques For Quinolinonesmentioning
confidence: 97%
“…By combining organocatalysis with photocatalysis through an asymmetric triple-reaction sequence, Xu et al reported a unique asymmetric approach for the synthesis of polycyclic indazole skeletons (Table 20A). 115 In this study, five consecutive chiral centers and five C–X bonds were used to create the stereoselective polycyclic indazole derivatives ( 713 ) in moderate to high yield. The α,β-unsaturated aldehyde ( 711 ) provided an imination reaction in the presence of CAT1 , and the Michael addition produced intermediate 726 in the presence of the indazole derivative ( 712 ).…”
Section: Alkenes As Synthonsmentioning
confidence: 99%
“…2 Till now, chemists have achieved the synthesis of many enantiomers, 3 but diastereoselective synthesis especially the multicomponent one is very difficult except for some cyclization reactions. 4 Because of the complex nature of multicomponent cascade reactions and the high activities of free radicals, 5 diastereoselective synthesis is extremely challenging. In addition, the intrinsic reason for the selective control of diastereoisomers in multicomponent photocatalytic reactions remains unclear.…”
mentioning
confidence: 99%